The Economics Efficiency of Cyprinus Carpio Growout Cultured In Running Water Pond - Lindawati Lindawati; Tajerin Tajerin (Universitas Islam Indonesia, 2009)
This study is estimating the production economic efficiency of running water pond, cultured-Cyprinus carpio growout. Primary data is analyzed using Cobb Douglas function approach.The result indicated that factors which significantly affected production were fishseed,fish-feed, and labor. The efficiency analysis showed that actual Cyprinus carpio growouthad not reached its efficient level, since input usage was below its optimum level, thusthe maximum profit was not gained. To be able to gain more profit, according to the calculationunder the optimum condition assumption, running water pond, cultured Cyprinus carpiogrowout had to reduce fish-seed usage while increasing fish-feed and labor usage.Keywords: efficiency, economic of scale, Cyprinus carpio growout, running-water-system